Performance of refrigerator operating with and without liquid-suction heating - Loh, Wing Liong (2012)
A modern refrigeration system consists of four main components which is a compressor, a condenser, an evaporator and a throttling device. There are many researches which have been conducted in order to achieve good performance of the refrigeration system such as two stage refrigeration system, energy systems and suction heating. Suction heating is based on the concept of heat transfer between the capillary tube and suction tube. Suction heating is applied in order to absorb heat and thus lowering the temperature if the refrigerant at the capillary tube. The main purpose of this project is to investigate the performance of refrigeration operating with and without liquid suction heating in order to investigate how much the suction heating influence the performance of the refrigeration system. The project is based on experimental study on refrigeration system test rig and two setup of experimental studies which is the experimental setup for refrigeration operating with suction heating and experimental setup for refrigeration operating without suction heating. Both sets of system configuration will be run until it reaches steady operating condition before data is collected in order to calculate the coefficient of performance (COP). Results show that the refrigeration system operating with liquid suction heating has the highest value of COP which is 2.14 compare with the system operating without suction heating which is 1.8. The percentage difference in COP is about 15.89 percent.